"When elephants fight, it is the grass that is crushed." A Critical Evaluation of the Treatment of Rape Victim-Witnesses by the International Criminal Court - Morris, Kara (Université d'Ottawa / University of Ottawa, 2013)
This thesis explores whether the developments in international law, exemplified by the Rome Statutes’ codification of numerous sexually violent war crimes and crimes against humanity, as well as the rights and protections afforded to victims, have been implemented as intended with respect to the treatment of rape victim-witnesses appearing before the International Criminal Court. Through a deductive content analysis of the court transcripts from The Prosecutor v. Jean-Pierre Bemba Gombo case currently before the court, it was determined that, with a few notable exceptions, many of the central strategies previously identified in the literature as disqualifying, limiting and discrediting the testimonies of rape victim-witnesses appearing before the International Criminal Tribunals for the former Yugoslavia and Rwanda, reemerged within the context of the International Criminal Court.